MEK and TGF-beta Inhibition Promotes Reprogramming without the Use of Transcription Factor - Vrbsky, Jan; Tereh, Tamas; Kyrylenko, Sergiy; Dvorak, Petr; Krejci, Lumir (PLoS One, 2015)
The possibility of replacing the originally discovered and widely used DNA reprogramming transcription factors is stimulating enormous effort to identify more effective compounds that would not alter the genetic information. Here, we describe the generation of induced pluripotent stem cells (iPSc) from head-derived primary culture of mouse embryonic cells using small chemical inhibitors of the MEK and TGF-beta pathways without delivery of exogenous transcription factors. These iPSc express standard pluripotency markers and retain their potential to differentiate into cells of all germ layers. Our data indicate that head-derived embryonic neural cells might have the reprogramming potential while neither the same primary cells cultivated over five passages in vitro nor a cell population derived from adult brain possesses this capacity. Our results reveal the potential for small molecules to functionally replace routinely used transcription factors and lift the veil on molecular regulation controlling pluripotency. The conditions described here could provide a platform upon which other genome non integrative and safer reprogramming processes could be developed. This work also shows novel potential for developing embryonic neural cells.
Keywords: diferenciační antigeny; Cellular Reprogramming; Animals; Antigens, Differentiation; Induced Pluripotent Stem Cells; přeprogramování buněk; indukované pluripotentní kmenové buňky; MAP Kinase Signaling System; MAP kinasový signální systém; Transforming Growth Factor beta; myši; zvířata; Mice; transformující růstový faktor beta